2021
DOI: 10.3390/ijms22041509
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Pancreatic β Cell Dysfunction in Diabetes

Abstract: Diabetes is a chronic metabolic disorder characterized by inappropriately elevated glucose levels as a result of impaired pancreatic β cell function and insulin resistance. Extensive studies have been conducted to elucidate the mechanism involved in the development of β cell failure and death under diabetic conditions such as hyperglycemia, hyperlipidemia, and inflammation. Of the plethora of proposed mechanisms, endoplasmic reticulum (ER) stress, mitochondrial dysfunction, and oxidative stress have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 145 publications
(190 reference statements)
4
125
0
3
Order By: Relevance
“…In addition, through generation of excess nitric oxide (NO), palmitate causes mitochondrial DNA damage-induced apoptosis in INS-1 cells [ 91 ]. Palmitate was also reported to trigger ROS production from diverse sources including the mitochondrial electron transport chain [ 92 ], peroxisomes [ 93 ], or due to NADPH oxidase activation [ 94 ]. A recent transcriptomic/proteomic profiling using INS-1E cells and isolated human islet data further suggested that palmitate may elicit an oxidative stress response in beta-cells [ 86 ].…”
Section: Molecular Mechanisms Involved In Beta-cell Apoptosismentioning
confidence: 99%
“…In addition, through generation of excess nitric oxide (NO), palmitate causes mitochondrial DNA damage-induced apoptosis in INS-1 cells [ 91 ]. Palmitate was also reported to trigger ROS production from diverse sources including the mitochondrial electron transport chain [ 92 ], peroxisomes [ 93 ], or due to NADPH oxidase activation [ 94 ]. A recent transcriptomic/proteomic profiling using INS-1E cells and isolated human islet data further suggested that palmitate may elicit an oxidative stress response in beta-cells [ 86 ].…”
Section: Molecular Mechanisms Involved In Beta-cell Apoptosismentioning
confidence: 99%
“…It has been reported that palmitate stimulates inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression and that the upregulation of these proteins causes mitochondrial dysfunction in beta cells [ 16 ]. Therefore, we evaluated the effect of AF-13 treatment on palmitate-stimulated inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic β-cells uptake STZ via Glut2 receptors, resulting in increased oxidative stress due to NO release and ROS production [ 22 ]. Pancreatic β-cells are typically prone to oxidative stress because of their relatively low expression of antioxidant enzymes [ 23 ]. Indeed, our data showed that INS-1 cells treated with STZ exhibited a dramatic increase in ROS and antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%